Studi Masyarakat Indonesia Tradisional, Transisi, Modern, Pedesaan dan Perkotaan - Irfan Azhari Ritonga; Noviani Noviani; Nurul Hidayah Napitupulu; Putri Wahyuni Sinaga (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2023)
The study of Indonesian society is always related to the condition of a pluralistic Indonesian society, both in terms of race, ethnicity and religion. In addition, the study of Indonesian society also has several sections including studies of traditional, transitional, modern Indonesian society, and studies of rural and urban communities. Traditional communities are usually referred to as rural communities, with a population of less than 2.500 people. A transitional society can be described as a society that is just experiencing growth, because in this transitional process, society is expected to be at a faster pace in understanding technological growth, which inevitably has to be able to master this technology. And in modern society, every level of society can be influenced by means of communication to convey information, such as radio and television. Meanwhile, rural and urban communities have a relationship of interdependence. With an illustration, urban communities need labor from rural communities, while rural communities need jobs created by urban communities. With the sections from the study of Indonesian society, the pluralism that has been formed long ago, can be seen clearly. Because each part of the study of society, has its own characteristics.Between village and traditional communities have the same characteristics. Because in the village community, there must be a strong sense of bond as well as traditional society. Whereas urban society has the same characteristics as modern society, because every urban society has an open view of new things, so it is not difficult for them to move forward to become a modern society. However, before achieving this, they must go through several phases, among which the first phase is called the colonial phase because it places leaders as foremen, the second phase is referred to as the developmental phase of administration and management because of the emergence of administrative and secretarial academics, the third phase is referred to as This phase is referred to as the global leadership phase, because leadership studies have begun to appear in specific fields.